Deciphering the smart city citizenship: the techno-politics of data and urban co-operative platforms - Calzada, I (Eusko Ikaskuntza, 2018)
The hegemonic ‘smart city’ approach in the European H2020 institutional framework is slowly evolving into a new citizen-centric paradigm called the ‘experimental city’. While this evolution incorporates social innovations—including urban co-operative platforms that are flourishing as (smart) citizens are increasingly considered decision-makers rather than data providers—certain underlying ethical and democratic issues concerning the techno-politics of data remain unresolved.